2008
DOI: 10.1021/ja800964g
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Structural Studies of 2′,3′-Difluorinated Nucleosides: Comparison of Theory, Solution, and Solid State

Abstract: The conformations of three 2′,3′-difluoro uridine nucleosides were studied by X-ray crystallography, NMR spectroscopy, and ab initio calculations in an attempt to define the roles that the two vicinal fluorine atoms play in the puckering preferences of the furanose ring. Two of the compounds examined contained fluorine atoms in either the arabino or xylo dispositions at C2′ and C3′ of a 2′, 3′-dideoxyuridine system. The third compound also incorporated fluorine atoms in the xylo configuration on the furanose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…However, the 2 -fluoro-β-d-dideoxyuridine molecules are reported with a coupling constant of 3.3 Hz for H1 -H2 [36] and in general, J H1 -H2 in β-nucleosides with a 2 -ara substituent is in the range of 3-4 Hz [37]. Barchi et al [38] reported the synthesis and conformational analysis of the 2 ,3 -dideoxy-2 ,3 -difluoro uridine analogues with the araand xylo-stereochemistry (Table S1), and the general trend of the values of the coupling constants mentioned above are in agreement with McAtee et al [37].…”
Section: Conformational Analysis Of the Synthesized Analoguesmentioning
confidence: 99%
“…However, the 2 -fluoro-β-d-dideoxyuridine molecules are reported with a coupling constant of 3.3 Hz for H1 -H2 [36] and in general, J H1 -H2 in β-nucleosides with a 2 -ara substituent is in the range of 3-4 Hz [37]. Barchi et al [38] reported the synthesis and conformational analysis of the 2 ,3 -dideoxy-2 ,3 -difluoro uridine analogues with the araand xylo-stereochemistry (Table S1), and the general trend of the values of the coupling constants mentioned above are in agreement with McAtee et al [37].…”
Section: Conformational Analysis Of the Synthesized Analoguesmentioning
confidence: 99%
“…Interestingly however, fluorinated isomer 23 is inactive against HIV reverse transcriptase, whereas the diastereomeric compound 24 maintains the potency of the parent compound 22 . This result can be explained by the effect of the fluorine atoms on the molecular conformations of 23 and 24 [ 24 ]. In isomer 23 , the fluorine atom aligns gauche to the ring oxygen, resulting in a C3′- endo ring pucker which is not recognised by HIV reverse transcriptase [ 24 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…This result can be explained by the effect of the fluorine atoms on the molecular conformations of 23 and 24 [ 24 ]. In isomer 23 , the fluorine atom aligns gauche to the ring oxygen, resulting in a C3′- endo ring pucker which is not recognised by HIV reverse transcriptase [ 24 25 ]. By contrast, in isomer 24 the fluorine once again aligns gauche to the ring oxygen, but this leads to a C3′- exo ring pucker which is known to be optimal for biological activity.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Marquez and co-workers previously observed similar extreme inclination of 2′,3′-dideoxy-2′,3′-FF- xylo uridine nucleosides towards C3′- endo conformation (~100% N). 32 …”
Section: Resultsmentioning
confidence: 99%